Identifying the extent and constraints of ICT adoption in the rural-based small and medium enterprises in Malaysia - Jaganathan, Mathivannan; Mahmood, Rosli; Ahmad, Shuhymee; Ahmad, Ismail (2013)
The purpose of this study is to identify the extent of ICT adoption among rural based SMEs in Malaysia and to understand the problems facing these SMEs in the implementation and usage of ICT. A quantitative research design based on the questionnaire survey was used to collect the data. A total of 1000 questionnaires were mailed and 167 usable responses were received.The findings reveal a relatively high adoption of ICT among rural based SMEs while lack of funds and financing were the main problems to the success of its adoption and implementation.The findings of this study may be of help to owner/managers of rural based SMEs and policy makers in Malaysia in finding solution to the successful adoption and implementation of ICT.